Предмет: Математика,
автор: petrushovasonya1
упростите выражение
а) (a-1)(a+3)-(a+1)^2
б) (x-y)(x+y)(x^2+y^2)
Ответы
Автор ответа:
0
упростите выражениеа) (a-1)(a+3)-(a+1)^2
(a-1)(a+3)-(a+1)^2=a²-a+3a-3-a²-2a-1=-4
б) (x-y)(x+y)(x^2+y^2)
(x-y)(x+y)(x^2+y^2)=(x^2-y^2)(x^2+y^2)=x⁴-y⁴
(a-1)(a+3)-(a+1)^2=a²-a+3a-3-a²-2a-1=-4
б) (x-y)(x+y)(x^2+y^2)
(x-y)(x+y)(x^2+y^2)=(x^2-y^2)(x^2+y^2)=x⁴-y⁴
Похожие вопросы
Предмет: История,
автор: privetpostruzusya
Предмет: Физика,
автор: nitfamilia
Предмет: Биология,
автор: galajdadzenni2
Предмет: История,
автор: Sakyrova
Предмет: Математика,
автор: adil2003